Ribosome profiling reveals translational regulation of mammalian cells in response to hypoxic stress - Zhiwen Jiang; Jiaqi Yang; Aimei Dai; Yuming Wang; Wei Li; Zhi Xie (BMC Genomics, 2017)
Abstract Background Retinal pigment epithelium (RPE) cells transfer oxygen and nutrients from choroid to the neural retina. Reduced oxygen to RPE perturbs development and functions of blood vessels in retina. Previous efforts of genome-wide studies have been largely focused on transcriptional changes of cells in response to hypoxia. Recently developed ribosome profiling provides an opportunity to study genome-wide translational changes. To gain systemic insights into the transcriptional and translational regulation of cellular in response to hypoxic stress, we used simultaneous RNA sequencing and ribosome profiling on an RPE cells line, ARPE-19, under hypoxia condition. Results Both HIF-1α and EPAS1 (HIF-2α) proteins were stabilized in ARPE-19 under hypoxic stress treatment at 1 h, 2 h and 4 h. Analysis of simultaneous RNA sequencing and ribosome profiling data showed genome-wide gene expression changes at both transcriptional and translational levels. Comparative analysis of ribosome profiling and RNA-seq data revealed that hypoxia induced changes of more genes at the translational than the transcriptional levels. Ribosomes densities at 5′ untranslated region (UTR) significantly increased under hypoxic stress. Interestingly, the increase in ribosome densities at 5′ UTR is positively correlated with the presence of upstream open reading frames (uORFs) in the 5′ UTR of mRNAs. Conclusion Our results characterized translational profiles of mRNAs for a RPE cell line in response to hypoxia. In particular, uORFs play important roles in the regulation of translation efficiency by affecting ribosomes loading onto mRNAs. This study provides the first attempt to understand translational response of mammalian cells under hypoxic condition.